2014
DOI: 10.1017/s135561771400099x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Environmental Dependency and Closing-in in Patients with Fronto-temporal Dementia

Abstract: Environmental dependency (ED) phenomena, including utilization behavior and imitation behavior, are clinical manifestations typically observed in patients with the behavioral variant of fronto-temporal dementia (bvFTD), who may also show the closing-in (CI) phenomenon. Here, we explored the neuropsychological correlates of ED and CI in bvFTD, and the association of ED with CI to clarify the mechanisms underlying these clinical manifestations. Thirty-one bvFTD patients underwent a wide cognitive assessment in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 31 publications
4
39
2
2
Order By: Relevance
“…Furthermore, correlated EF factor domains provide evidence for a general EF factor, which may reflect a central executive function (see example with D-KEFS in Latzman, Elkovitch, Young & Clark, 2010). Evidence for a general EF factor has also been provided by Li et al (2014) based on a sample of adolescents (N= 142, 12-18 years) who were administered the D-KEFS. Moreover, as noted by Crawford et al (2011) the use of a general EF composite also has the advantage of providing greater reliability of EF assessment, given that the individual D-KEFS scores have lower reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, correlated EF factor domains provide evidence for a general EF factor, which may reflect a central executive function (see example with D-KEFS in Latzman, Elkovitch, Young & Clark, 2010). Evidence for a general EF factor has also been provided by Li et al (2014) based on a sample of adolescents (N= 142, 12-18 years) who were administered the D-KEFS. Moreover, as noted by Crawford et al (2011) the use of a general EF composite also has the advantage of providing greater reliability of EF assessment, given that the individual D-KEFS scores have lower reliability.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, one retrospective study showed that CI is as frequent in AD as in FTD patients, but did not provide qualitative observations [187]. Indeed, in a sample of patients with the behavioral variant of FTD, near-CI has been observed more frequently than adherent-CI, and was often (but not obligatorily) associated with other imitation and utilization behaviors [188]. Notably, more frequent occurrence of near-CI than of adherent-CI has been recently reported also in non-demented Parkinson's disease patients [189], whereas the reverse pattern has been observed in Parkinson's disease dementia [190].…”
Section: Closing-inmentioning
confidence: 96%
“…Several cross‐sectional and longitudinal studies have demonstrated abnormalities in brain structure and function, particularly in chemotherapy‐treated patients and survivors (D'Agata et al., 2013; Deprez et al., 2014; Jung et al., 2016; Kesler & Blayney, 2015; Lepage et al., 2014; Nudelman et al., 2014; Simo et al., 2015; Stouten‐Kemperman et al., 2014). However, many patients demonstrate differences in brain structure and function prior to chemotherapy suggesting that cancer pathogenesis, surgery/anesthesia, disease burden, host‐related, and/or other factors may contribute to early brain changes (Cimprich et al., 2010; McDonald, Conroy, Ahles, West, & Saykin, 2012; Menning et al., 2015; Sato et al., 2015; Scherling, Collins, Mackenzie, Bielajew, & Smith, 2012; Scherling, Collins, Mackenzie, Lepage, et al., 2012).…”
Section: Introductionmentioning
confidence: 99%